Effect of Small Peptide Chelate Chromium on Growth Performance, Organ Development and Serum Traits in Spargue-Dawley Rats - Jin, Chen; Zhi-Sheng, Wang; An-Guo, Zhou (Pakistan Journal of Nutrition, 2009)
The experiment was conducted to study the effect of supplementing Small Peptide Chelate Chromium (SPCr) in diets on growth performance, organ development and serum traits in Spargue-Dawley rats. Seventy two SD rats with initial body weight about (65±5 g) were randomly assigned to six dietary treatment, basal diet, basal diet supplemented with 100, 200, 500 or 1000 μg/kg Cr in the form of SPCr and 200 μg/kg Cr in the form of chromium picolinate (CrPic). Each treatment had 6 replicates. The duration of the study was 35 days. The results showed that: Supplementation of Cr with different types at low-level (below 500 μg/kg) increased daily gain and feed efficiency. Supplementation of 500 μg/kg SPCr increased ADG (p<0.05), decreased feed:gain ratio (p<0.05) compared with control group. Serum cholesterol and triglyceride was decreased(p<0.05) fed diets with SPCr at low-level. Supplementation of Cr with different types increased serum high density lipoprotein (p<0.05), also decreased serum glucose and insulin compared with control group. Addiction of Cr with different types increased the relative weights of liver (p<0.05). It was concluded that SPCr had effect to improve performance and serum lipids.